EFFECT OF INSULATION MATERIAL THICKNESS ON THERMAL INSULATION - Ozkan, Derya B.; Onan, Cenk; Erdem, Serkan (YILDIZ TECHNICAL UNIV, 2009)
In our country, Thermal Insulation Requirements for Buildings was implemented to save energy in buildings in 2000. By insulating the buildings, the required heating energy is decreased and energy saving is provided. Determining the correct material and optimum insulation thickness are very important issues in thermal insulation. In this study, software is developed according to TS 825 and charts which show optimum insulation thickness for different insulation materials are drawn for 4 different regions of Turkey. Moreover, in the study the effect of change in window and wall area to building heat energy requirement and optimum thickness is investigated.
Keywords: Insulation thickness; TS 825; thermal insulation; energy efficiency; Engineering